«Abbiamo lasciato il campo cantando» - Rizzuti, Marida (Mimesis Journal, 2017)
Jewish cabaret in the concentration camps during 1939-1945. The author, while only concentrate on life in two elds (Westerbork and Theresienstadt), is able to provide the tragic dimension of the annhilament of European Jews, their extreme resistance nds the highest expression into the comical, the cabaret. The author does not always nd an answer to the dramatic questions, that come to light from the book, but it is an appropriate starting point for future insights.